Education Transformation in Palangka Raya: Optimizing Technology Management through Artificial Intelligence Towards Quality Improvement - Berkat (JTP - Jurnal Teknologi Pendidikan, 2024)
The aim of this research is to determine the role of artificial intelligence (AI) in education, especially in the field of institutional education. Specifically, the aim of this research is to answer the role of AI in helping students and teachers find new teaching materials that are more efficient and effective in increasing student competence. The method used is a literature study using a systematic literature review approach. In a systematic literature review, all reading is analyzed and placed in the preparation of background, theory and discussion. The number of journals used was 35 journals, some of which were books and other online manuscripts. Data were analyzed using five steps, namely tracing primary and secondary sources; data processing/citation of references; presenting data; interpret data; and draw conclusions. The research results found that artificial intelligence has gained widespread acceptance and use in the field of education, especially in the field of institutional education which is the main topic of this research. The research also found that AI robots can now be used as stand-alone co-teachers or educators, as well as robots to perform similar tasks to educators or instructors. Utilization of these resources has been able to increase the efficiency and effectiveness of educators, so that the quality of teaching is richer or better. Furthermore, the research results found that, artificial intelligence has given students access to a better learning experience because Artificial Intelligence allows the adjustment of learning resources according to students' needs and abilities. In general, the research results found that, artificial intelligence has influenced education significantly, especially in the fields of management, teaching and learning both in the educational sector or personal situations teaching educational institutions.